Simultaneous quantitative analysis and in vitro anti-arthritic effects of five polyphenols from Terminalia chebula - Liu, Fang; Zhan, Shipeng; Zhang, Pu; Jia, Changsheng; Zhu, Qingzong; Dai, Qing; Yu, Mingjie; Cheng, Lin; Xiong, Lirong; Sun, Fengjun; Xia, Peiyuan; Zhang, Xiao; et al. (Frontiers in Physiology, 2023)
Background: The fruit of Terminalia chebula has been widely used for a thousand years for treating diarrhea, ulcers, and arthritic diseases in Asian countries. However, the active components of this Traditional Chinese medicine and their mechanisms remain unclear, necessitating further investigation. Objectives: To perform simultaneous quantitative analysis of five polyphenols in Terminalia chebula and evaluate their anti-arthritic effects including antioxidant and anti-inflammatory activity in vitro. Materials and Methods: Water, 50% water-ethanol, and pure ethanol were used as extract solvents. Quantitative analysis of gallic acid, corilagin, chebulanin, chebulagic acid, and ellagic acid in the three extracts was performed using high-performance liquid chromatography (HPLC). Antioxidant activity was assessed by the 2,2-diphenylpicrylhydrazyl (DPPH) radical-scavenging assay, and anti-inflammatory activity was evaluated by detecting interleukin (IL)-6 and IL-8 expression in IL-1β-stimulated MH7A cells. Results: The 50% water-ethanol solvent was the optimal solvent yielding the highest total polyphenol content, and the concentrations of chebulanin and chebulagic acid were much higher than those of gallic acid, corilagin, and ellagic acid in the extracts. The DPPH radical-scavenging assay showed that gallic acid and ellagic acid were the strongest antioxidative components, while the other three components showed comparable antioxidative activity. As for the anti-inflammatory effect, chebulanin and chebulagic acid significantly inhibited IL-6 and IL-8 expression at all three concentrations; corilagin and ellagic acid significantly inhibited IL-6 and IL-8 expression at high concentration; and gallic acid could not inhibit IL-8 expression and showed weak inhibition of IL-6 expression in IL-1β-stimulated MH7A cells. Principal component analysis indicated that chebulanin and chebulagic acid were the main components responsible for the anti-arthritic effects of Terminalia chebula. Conclusions: Our findings highlight the potential anti-arthritic role of chebulanin and chebulagic acid from Terminalia chebula.